Addressing the Challenges of Extension and Advisory Services in Uganda: The Grameen Foundation’s Community Knowledge Worker Program - Daniel McCole; Michael J. Culbertson; Murari Suvedi; Paul E. McNamara (Journal of International Agricultural and Extension Education, 2014)
Diffusion of agricultural knowledge is vital to food security and capacity building in the developing world. Many developing world farmers still do not have access to extension and advisory services (EAS), and poor agricultural practices still exist. Diffusion of agricultural knowledge could lead to improved productivity, higher obtained prices, and increased incomes, but it is made more difficult in the developing world by poor infrastructure, high illiteracy rates, and too few extension agents. The rapid spread of mobile phones throughout the developing world has sparked many EAS programs that incorporate mobile technologies. Although they offer great potential for knowledge diffusion, research has not yet identified strong positive impacts of mobile technology-based interventions. The Grameen Foundation’s Community Knowledge Worker (CKW) program provides model farmers in Ugandan communities with training and smartphones that are linked to a database with actionable agricultural information. The model farmers (CKWs) interact with their neighbors to share the information in the database. This relatively inexpensive program differs from other EAS initiatives by using a large number of lightly trained “extension agents” and mobile technology that provides those agents with easy-to-access information they share with and help interpret for the farmers in their communities. The program also incorporates ongoing data collection via the smartphones, allowing for a two-way exchange of information and enabling constant monitoring. Two recent studies have shown this program to have positive impacts. An ongoing randomized control trial promises to offer a comprehensive impact assessment
Keywords: agricultural extension and advisory services; international development; Uganda; information and communication technology (ICT); knowledge diffusion